Problem oddziaływań orientalnych i egejskich w epoce brązu na obszarze kręgu nordyjskiego w świetle najnowszejliteratury - Zaleska, Jolanta (Acta Universitatis Lodziensis. Folia Archaeologica, 1990)
The paper discusses the problem of oriental and Aegean influences in the area of Nordic cultures mainly based on the article by P. Schauer. The author concludes that this article being in the literature of the subject one of the latest in not the only attempt of explaining this phenomenon, is the complex expression of the idea, yet it does not comprise the whole of this issue.